Cardio-Respiratory Effects of Air Pollution in a Panel Study of Outdoor Physical Activity and Health in Rural Older Adults. Issue 4 (April 2017) - Stieb, David M.; Shutt, Robin; Kauri, Lisa; Mason, Sarah; Chen, Li; Szyszkowicz, Mieczyslaw; Dobbin, Nina A.; Rigden, Marc; Jovic, Branka; Mulholland, Marie; Green, Martin S.; Liu, Ling; et al.
Abstract : Objective: To examine cardio-respiratory effects of air pollution in rural older adults exercising outdoors. Methods: Adults 55 and over completed measurements of blood pressure, peak expiratory flow and oximetry daily, and of heart rate variability, endothelial function, spirometry, fraction of exhaled nitric oxide and urinary oxidative stress markers weekly, before and after outdoor exercise, for 10 weeks. Data were analyzed using linear mixed effect models. Results: Pooled estimates combining 2013 ( n  = 36 participants) and 2014 ( n  = 41) indicated that an interquartile increase in the air quality health index (AQHI) was associated with a significant ( P  < 0.05) increase in heart rate (2.1%) and significant decreases in high frequency power (−19.1%), root mean square of successive differences (−9.5%), and reactive hyperemia index (−6.5%). Conclusions: We observed acute subclinical adverse effects of air pollution in rural older adults exercising outdoors. Abstract : Supplemental Digital Content is available in the text